THE CONCEPT AND ESSENCE OF HUMAN RIGHTS AFTER DEATH: THEIR PLACE IN THE SYSTEM OF CIVIL RIGHTS OBJECTS - Khaydarova Khilola Anvarovna (Bright Mind Publishing, 2025)
This article explores the concept and essence of human rights after death, examining their role within the framework of civil rights. It addresses the complexities surrounding posthumous rights, including inheritance rights, the protection of personal dignity, and non-property rights. The discussion highlights the ongoing relevance of these rights in contemporary society, particularly in light of evolving legal and social contexts. The article presents various perspectives on the existence and transferability of human rights post-mortem, emphasizing the challenges heirs face in protecting the rights of the deceased. Additionally, it identifies specific categories of posthumous rights and the legal norms governing them. Ultimately, this work underscores the necessity for legal protection of human rights after death, advocating for a balanced approach that respects both individual dignity and societal values.
Keywords: Posthumous human rights, inheritance rights, protection of honor and dignity, non-property rights, civil rights system, legal protection.